2021
DOI: 10.1186/s12876-021-01925-z
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal metastasis of renal cell carcinoma resected by endoscopic submucosal dissection: a case report

Abstract: Background Esophageal metastasis of renal cell carcinoma (RCC) is extremely rare. We have described herein a case of a 59-year-old man with esophageal metastasis of RCC that was endoscopically resected. Case presentation The case was a 59-year-old man who had undergone left nephrectomy for renal clear cell carcinoma 17 years ago and splenectomy for splenic metastasis 3 years ago. Esophagogastroduodenoscopy (EGD) performed 9 years ago revealed a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…The time to metastatic relapse is variable, usually several years after surgical treatment. Our case report has an early filing of 4 months, which is below the average (24 months) in a series of cases [1] and for other case reports [2,[7][8][9], also the initial size of the mass is unusual with a commitment of 100% of the lumen, which is greater than the reported cases, where a solitary nodule or polyp is generally reported that does not occupy the entire esophageal diameter [2,9,10], the treatment is multidisciplinary, with surgical treatment as the first option and a combination of radiotherapy and chemotherapy [8,9], with the increasingly widespread use of tyrosine kinase inhibitors such as pazopanib [2][3][4][5][6], or checkpoint inhibitors.…”
Section: Ccrc: Clear Cell Renal Cell Carcinomacontrasting
confidence: 65%
See 2 more Smart Citations
“…The time to metastatic relapse is variable, usually several years after surgical treatment. Our case report has an early filing of 4 months, which is below the average (24 months) in a series of cases [1] and for other case reports [2,[7][8][9], also the initial size of the mass is unusual with a commitment of 100% of the lumen, which is greater than the reported cases, where a solitary nodule or polyp is generally reported that does not occupy the entire esophageal diameter [2,9,10], the treatment is multidisciplinary, with surgical treatment as the first option and a combination of radiotherapy and chemotherapy [8,9], with the increasingly widespread use of tyrosine kinase inhibitors such as pazopanib [2][3][4][5][6], or checkpoint inhibitors.…”
Section: Ccrc: Clear Cell Renal Cell Carcinomacontrasting
confidence: 65%
“…Esophageal metastases from CCRC of clear cell variants are even rarer. Seven cases have been described in the literature, including our case report, which are shown in Table 1 [ 1 , 2 , 6 - 10 ]. Esophageal metastasis of RCC is extremely rare and there is not clear evidence why they appear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastatic esophageal cancer is very rare clinically. Since the first case of metastatic esophageal cancer from the prostate was reported by Gross et al (16) in 1942, various metastatic esophageal cancers in different organs have been reported, including the breast, lungs, ovary, liver, colon, pancreas, bladder, kidneys, and stomach (17)(18)(19)(20)(21)(22)(23)(24)(25). The most common primary sites for metastatic esophageal cancer are the breast and lungs (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…According to epidemiological survey data, the incidence of esophageal carcinoma ranks eighth among all malignant tumors worldwide [ 3 ], the incidence in East Asia has been consistently higher than the world average due to the special dietary habits, and in China in 2018, new cases and deaths of esophageal carcinoma accounted for 53.7% and 55.7% of the global total, respectively, with esophageal carcinoma burden about two times the world level [ 4 , 5 ]. Early diagnosis and treatment is key to reducing such burden in China [ 6 , 7 ]. Currently, endoscopy, a set of devices for the diagnosis and treatment of digestive diseases by direct acquisition of images of the alimentary tract and digestive organs through the alimentary tract, has become a main method for diagnosis of early esophageal carcinoma in practice.…”
Section: Introductionmentioning
confidence: 99%